Pengaruh Penerapan Blue Ocean Strategy Terhadap Daya Saing Pada Usaha Mikro Kecil Menengah (UMKM) Restoran - Aryati Fatmi; Mukaram Mukaram (Jurnal Riset Bisnis dan Investasi, 2015)
The purpose of this study is to investigate the role of blue ocean strategy towards competitiveness. Through increasing number of UMKM in Bandung, business competition has become very tight including in restaurant businesses. In order to acquire high competitiveness, UMKM-based restaurants in Bandung need a business strategy to survive. One of the effective business strategies is blue ocean strategy. Blue ocean strategy is a business strategy of which the main key implementation is to carry out value innovation so that company can create market space wherein without any competitors yet. This condition makes company capable of improving its competitiveness. The measurement of blue ocean strategy application level covers product utility dimension, product price tag, production target cost, and adoption retarder. Meanwhile, the measurement of competitiveness level applies human resources dimension, availability and mastery in information and technology, and management and organization. This research uses non-probability sampling method with purposive sampling technique. This research uses 101 restaurants as sample out of 468 populations. The respondents of this research are owner, manager and supervisor. The findings show that the blue ocean strategy contributes 41.8% to the competitiveness of the UMKM restaurants in Bandung.Keywords: Competitiveness, Value Innovation, Restaurant, Business Strategy, Micro, Small and Medium Enterprises.